Production of solid fuel with torrefaction from agricultural wastes - Duranay, Neslihan Deveci; Çaycı, Nazlı (MIM RESEARCH GROUP, 2019)
In this study, it was aimed to produce solid fuel by applying torrefaction process to agricultural wastes, left in the field (usually left to decay) after harvest or post-cultivation period. An eggplant stalk left in the field as an agricultural waste after production period was used in the study. The torrefaction process was applied to the original plant parts cut in certain lengths, and also to the pellets prepared from the same plant. The torrefaction experiments were performed in a pyrex glass reactor placed inside a vertical cylindrical refractory chamber, through which resistance wires are passed. The torrefaction process was performed in N2 atmosphere at the operation temperatures of 220, 260 and 300oC. The proximate and elemental analyses of the solid product were performed. Besides, the energy yield was determined by measuring the higher heating values (HHV) of the original sample and solid product. Depending on torrefaction temperature ıt was determined a decrease in the solid product yield, an increase in the yields of liquid and gas products. While the volatile matter content of the solid product was decreased, it was found that the rate of fixed carbon increased. It was also determined that elemental carbon ratio increased and oxygen ratio decreased as a result of the torrefaction process. It was detected that the higher heating value of the biomass increased with rising torrefaction temperature and 65.58% of the energy that contained has been maintained at severe (300°C) torrefaction conditions. © 2019 MIM Research Group. All rights reserved.
Keywords: Agricultural waste; Biomass; Energy yield; Torrefaction